2011
DOI: 10.1007/s11882-011-0223-6
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity and the Role of Defensins in Otitis Media

Abstract: Otitis media is the most common pediatric disease in developed countries and a significant cause of morbidity and hearing loss in developing countries. The innate immune system is essential to protecting the middle ear from infection. Defensins, broad-spectrum cationic antimicrobial peptides, have been implicated in prevention of and the early response to acute otitis media; however, the mechanisms by which defensins and other antimicrobial molecules mediate this protection have not been completely elucidated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…They also identify the resting ME cells that express major determinants of innate immunity. As noted above, innate immunity is responsible for the normal resolution of OM (e.g., Underwood and Bakaletz, 2011;Kurabi et al, 2016). The immediate response provided by the cell of the normal ME is critical to initiating this first line of defense against infection.…”
Section: Discussionmentioning
confidence: 99%
“…They also identify the resting ME cells that express major determinants of innate immunity. As noted above, innate immunity is responsible for the normal resolution of OM (e.g., Underwood and Bakaletz, 2011;Kurabi et al, 2016). The immediate response provided by the cell of the normal ME is critical to initiating this first line of defense against infection.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TNF-αcan modulate the expression of Toll-like receptors (TLR) and is also essential for TLR signaling, including nuclear factor (NF)-κB, via both positive [7] and negative [8] feedback mechanisms. Recent data illustrate a critical role for TLR2 and TLR4 signaling via a MyD88-dependent pathway in the middle ear inflammatory responses to bacteria, and they are particularly important during the recovery process from OM [9]. Thus, MIF can indirectly trigger inflammatory responses in OM through TNF-α.…”
Section: Introductionmentioning
confidence: 99%
“…These genes encode peptides or proteins that are involved in host defense against bacterial infection, and the down-regulation in co-treatment indicates that the host defense was decreased. Defensins are broad-spectrum antimicrobial peptides that have been implicated in prevention of AOM (Underwood and Bakaletz, 2011). It was reported that deficiency of S100A8/A9 in mice could promote the progression of pneumonia caused by bacterial infection (Achouiti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%